Determining the effects of 2-ethylhexyl nitrate blend on isolated diesel engine attributes using the experimental and ANN approaches - Sevinc, Huseyin; Hazar, Hanbey (Taylor & Francis Inc, 2022)
This study examines the effects of 2-ethylhexyl nitrate (2EHN) blend on performance parameters of a diesel engine coated with Cr2O3 by comparing the experimental and ANN approaches. Piston, exhaust, and intake valves of the diesel engine were coated with Cr2O3 in 300-mu m thickness. 2EHN was added into diesel fuel at 3%, 6%, 9% (vol.) ratios, and DE3, DE6, and DE9 blends were produced. The training and testing data of ANN were acquired from exhaust gas temperature (EGT), brake specific fuel consumption (BSFC) and engine vibration (EV) values obtained from the coated engine (CE) and uncoated engine (UE). In addition, brake thermal efficiency (BTE) was calculated and the thermal images were taken to see the coating effects more clearly. The engine tests showed that EGT, BTE, and EV values increased in CE; whereas, SFC values decreased compared to UE. In both CE and UE, the addition of 2EHN reduced SFC, but EGT, BTE, and EV values increased. Thermal images supported the changes in parameters in both CE and UE. ANN results showed that performance parameters can be estimated with low error rates. The lowest regression (R) values were obtained as 0.9939, 0.96255, and 0.99199 for EGT, SFC, and EV, respectively.
Keywords: Thermal barrier coating; 2-ethylhexyl nitrate; diesel engine; engine performance; artificial neural network